Integrating Viewpoint and Space: How Lamination across Gesture, Body Movement, Language, and Material Resources Shapes Learning. Issue 3 (3rd July 2021) - DeLiema, David; Enyedy, Noel; Steen, Francis; Danish, Joshua A.
Abstract: Gesture is recognized as part of and integral to cognition. The value of gesture for learning is contingent on how it gathers meaning against the ground of other relevant resources in the setting—in short, how the body is laminated onto the surrounding environment. With a focus on lamination, this paper formulates an integrated theory of viewpoint and spatial reasoning; develops an embodied approach to documenting and understanding the live construction of students' spatial models; and offers new implications for the teaching of spatially complex concepts. We start with a study of how undergraduate students playfully gesture the first-person movements of components of an engineering system, step out to depict how the system appears from the outside, and all the while track how the components of the system spatially interact in the open canvas of empty space around the body. Students who manage all three—switching from character viewpoints to observer viewpoints while maintaining a coherent organization of space—better learn the engineering concept. We then examine this process in the unscripted discourse of a classroom of 1 st and 2 nd graders pretend-playing as bees. This second study extends the analysis of interactions between spatial reasoning and viewpoint into unplanned teacher-student discourse (including adjustments in talk and action over time) and a materially rich setting. In all, the paper formulates an embodied learning framework that integrates viewpoint and spatial reasoning with implications for learning design.